The Influence of Pai Teachers' Symbolic Communication In Forming Students' Religious Awareness In The Era of Digital Disruptions - Siti Annisak (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to determine the effect of symbolic communication of Islamic Religious Education (PAI) teachers on students' religious awareness in the era of digital disruption at MA Al-Anwar 2. The approach used in this study is quantitative with a survey method. Data collection techniques were carried out through observation, questionnaires, and documentation with a total of 35 students as respondents. Data analysis used the IBM SPSS Statistics application which includes descriptive statistical tests, normality tests, Pearson correlation tests, coefficients of determination, simple linear regression, and t-tests. The results of the study indicate that there is a positive and significant influence between symbolic communication of Islamic Religious Education (PAI) teachers on students' religious awareness, as evidenced by a significance value of 0.019 <0.05 and a correlation coefficient value of 0.393. In addition, the coefficient of determination shows a contribution of 15.5% to the variable of students' religious awareness, while the rest is influenced by other factors such as family environment, peers, and digital media. Thus, the better the symbolic communication of Islamic Religious Education (PAI) teachers, the higher the students' religious awareness in the era of digital disruption.